Analisis Budaya Kerja Etnik pada Kelompok Sadar Wisata Dalam Pengelolaan Ekowisata Sungai Bangek di Kota Padang - Ratri Alfadira; Frinaldi, Aldri (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Ethnic work culture is a value that originates from a particular ethnicity which is recognized as a distinctive character at work. This research aims to find out how the ethnic work culture of the tourism awareness group is in managing the Sungai Bangek Nature Park in the city of Padang. This research uses descriptive qualitative methods with data analysis techniques in the form of SWOT analysis. The object of this research is the Sungai Bangek Nature Park and Nature Tourism Awareness Group. The results of this research show that the ethnic work culture of the Sungai Bangek Nature tourism awareness group (Pokdarwis) is very influential in the management of the Sungai Bangek Nature Park in Padang City. The Pokdarwis ethnic work culture is influenced by the characteristics and ethnic background of the members of the group, where in the management of Sungai Bangek Nature Park, currently the Pokdarwis ethnic work culture has an individualistic, egalitarian and converse work culture, while creative work culture does not yet exist in the management of Sungai Bangek Nature Park.